Extrahepatic manifestations of chronic hepatitis B at the Centre National Hospitalier et Universitaire Hubert Koutoukou Maga in Cotonou in 2017. - KPOSSOU, PAUL (My University, 2023)
Introduction: Extrahepatic manifestations (EEM) are frequently encountered in chronic viral hepatitis. The aim of this study was to determine the prevalence of MEH in chronic viral hepatitis B (CVH) and to identify factors associated with these manifestations. Materials and methods: This was a descriptive and analytical cross-sectional study conducted from May 15 to August 31, 2017. Data were collected prospectively on the basis of the results of clinical examinations and paraclinical examinations of patients with HVB who consulted us during this period. Results: A total of 121 patients with HVB were included. Of the 121 patients with HVB, MEH was found in 103 patients (85.1%). These MEH were clinical (MCEH) in 86 patients (71.1%), and biological (MBEH) in 57 patients (47.1%). The main MCEH were asthenia (58.7%), arthralgia (27.3%), dermatological manifestations (17%) and paresthesias (12.4%). Biological manifestations included renal impairment (33.8%) and thrombocytopenia (25.6%). None of the factors studied was associated with the presence of extrahepatic clinical manifestations of HVB. However, age and antiviral treatment were associated with the presence of renal involvement (p= 0.011). Conclusion: MEH was present in the majority of chronic HVB carriers, and was dominated by asthenia. However, no factor was associated with the presence of extrahepatic clinical manifestations; whereas age and antiviral treatment were associated with the existence of an extrahepatic biological manifestation
Keywords: hepatitis B; extrahepatic manifestations; associated factors; Cotonou